A compositional explanatory theory of pedophilia. (November 2021) - Gannon, Theresa A.
Abstract: A key problem associated with adequate knowledge generation in pedophilia is that theories and studies predominantly examine abusive pedophilia. Acting abusively in relation to children—even where pedophilia is present—is likely to involve a different set of processes to those involved in the underlying concept of pedophilia itself. What is required is a consistent definition of pedophilia, as well as an explanation of its composition, to promote insight into the etiological mechanisms underpinning pedophilia independent of abusive behavior. In this manuscript, I critically review both the concept of pedophilia and existing pedophilia theory. Then, using the Phenomena Detection Method of Theory Construction (PDM-TC; Ward & Clack, 2019), I generate a compositional explanatory theory of pedophilia (CEToP). The CEToP examines the composition and possible causes of pedophilia via an overarching framework that specifies two key pathways as being responsible for the central clinical features of pedophilia and reconciles biological and environmental explanations of pedophilia. I examine this new theory according to key evaluative components associated with theory construction and conclude by highlighting the CEToPs potential application for research and practice with individuals experiencing pedophilia. Highlights: This manuscript critically reviews the concept of pedophilia and existing pedophilia theory. A compositional theory of pedophilia (CEToP) is proposed. The CEToP explains the concept of pedophilia itself rather than abusive action. The CEToP specifies two key pathways as being responsible for the central clinical features of pedophilia.